Determinan Kepatuhan Minum Obat Gagal Jantung - Oktavina, Risa; Jumaiah, Wati; Purnamawati, Dewi; Sofyani, Yani; Sumedi, Sumedi (Journal of Telenursing (JOTING), 2023)
This study aims to determine the factors influencing medication adherence in heart failure patients at Persahabatan Hospital. The research method used is observational analytics with a cross-sectional study approach using a retrospective system. The results showed that the characteristics of respondents who adhered to taking medication were 78 people (56.1%). Factors that are significantly related to medication adherence are anxiety and family support, and the most dominant variable is the Anxiety variable (p-value: 0.018., OR: 3.157., 95%CI 1.220 – 8.171). In conclusion, the more optimal the family support received by the respondent, the better their compliance with treatment. The more the respondent does not experience anxiety, the more obedient the respondent is in taking medication. Keywords: Determinants of Compliance with Medication, Heart Failure.